Redesign of a fault indicator unit / Muhammad Kamal Abu Bakar - Abu Bakar, Muhammad Kamal (1996)
A redesign process of an existing fault indicator system is presented. This system is manufactured by Elektro-Mechanik GMBH (Germany) with Surface mounting Housing (outdoor). Synthesis and logical methods are introduced to achieve the target. The design process are to localize the system which make use of local material. A comparison of the results had been done between the logical and the original system.